(untitled) (Eurasian Medical Research Periodical, 2023)
The main task of diagnostics is to identify pathology at the earliest possible stages of its development, before the appearance of severe forms and complications. However, given the low awareness of the population and the long-term chronic course of periodontal diseases, patients with advanced periodontitis at a severe stage seek treatment. In these conditions, individual assessment and prediction of the risk of periodontitis in patients with arterial hypertension is relevant. Such studies will serve as a basis for identifying patients with a high risk of developing periodontal diseases, grouping them for the purpose of dental monitoring and implementing measures to neutralize the negative effects of periodontal diseases on the course of hypertension.